STUDI KASUS TENTANG SISWA YANG MEMILIKI PERILAKU PROKRASTINASI AKADEMIK PADA SISWA KELAS XI AP SMK NEGERI 3 PONTIANAK - Riyadah, Riyadah; Astuti, Indri; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research entitled case study about students who are difficult to academic procrastination behavior in class XI SMK Negeri 3 Pontianak.The general problem in this research is how to help learners who are difficult to academic procrastination behavior in class XI SMK Negeri 3 Pontianak. While the objective is to obtain an objective picture of the characteristics, factors causing, and appropriate alternative assistance to be used in overcoming the problems of students who are difficult to academic procrastination behavior in class XI SMK Negeri 3. The approach used in this research is qualitative by using descriptive method and the form of research is case study. There are two case subjects in this study, the alternative aid given to the first subject is in the form of treatment using conceptual modeling techniques so that the behavioral of the subject can shape new behavioral better. While alternative assistance is given to the second, the case subject is treatment by using behavioral disputation in the REBT counseling model so that case subjects can change their irrational mindset into a rational mindset.Â Keywords: Difficult to Academic Pocrastination, Behavioral Counseling, REBT Counseling